The effect of small-sided games using the FIT LIGHT training system on some harmonic abilities and some basic skills of basketball players - Hassan, Ahmed K.; Alibrahim, Mohammed S.; Sayed Ahmed, Yasser Abdul Rashid (Frontiers in Sports and Active Living, 2023)
The aim of this research is to identify the effect of Small-sided games using the FIT LIGHT training system on some of the harmonic abilities and some of the basic skills of basketball Players. The researchers used the experimental method on 24 basketball players. They were randomly divided into two groups: one experimental (n = 12, age = 10.92 ± 0.79 years; height = 138.50 ± 2.78 cm; weight = 40.25 ± 2.01 kg) and a control group (n =12, age = 11.17 ± 0. 72 years; length = 139.92 ± 3. 53 cm; weight = 40.50 ±. 1.73 kg). The homogeneity between the two groups was calculated and showed that there were no differences between the two samples. In the research variables, the proposed program was applied for 10 weeks at the rate of 4 weekly training units. The proposed training program had a positive impact on the harmonic abilities and basic skills of basketball players and the differences in improvement rates for all variables were in favour of the experimental group. Therefore, the research suggests that Small-sided games using FIT LIGHT positively affect all the variables under research. This leads to significant differences between the post-tests and benefits the experimental group.